Make money with condominiums and townhouses - Eldred, Gary W. (John Wiley, 2003)
In the Make Money series, renowned real estate investor and bestselling author Gary W. Eldred shows you how to profit from the safest, most reliable wealth builder in the world–real estate. With coverage of all the fundamentals–from finding the right properties to financing and managing them–Eldred shows you the ropes so you don’t have to learn important lessons the hard way. Unlike general guides to investing in real estate, each title in the Make Money series gives you the specialized expertise necessary to fully profit from a select investment strategy.